Going beyond borders after a pandemic: Preparedness of teachers to embrace E-learning in a small Philippine university - DYANIKA NOLASCO; DANISSE MAE HERNANDEZ (CTU Journal of Innovation and Sustainable Development)
The global pandemic posed considerable challenges to education, necessitating educators to adopt various teaching methods, particularly those conducted through online platforms. To do this effectively, teachers needed readiness, skills, and dedication. A study was undertaken with 119 higher education teachers from different fields in a state institution, using both surveys and interviews to collect data. The findings revealed that these instructors were prepared for online teaching as they had the necessary devices, such as cell phones and laptops, access to wireless internet, and moderate internet speed, though it sometimes became slow when multiple devices were connected. The faculty exhibited proficient technological skills, making them competent in using technology. Despite difficulties, they displayed a positive attitude and efficient time management. The study suggests that teachers' readiness to adopt e-learning as an alternative to traditional classroom teaching could be a powerful solution to the significant challenges posed by the pandemic. Teachers' ability to adapt and embrace online teaching, supported by their technological proficiency and positive mindset, is seen as a potential remedy to the educational obstacles during the pandemic. Their preparedness to navigate this shift may offer a way to overcome the difficulties encountered in the education sector during these unprecedented times.